Proses Pelepasan Mora Pada Bahasa Jepang Dalam Novel Narcissu Karya Tomo Kataoka - Hadiid Hideo Nusantara; Nandang Rachmat; Riza Lupi Ardiati (KIRYOKU, 2021)
This article discusses the Mora disspation process in Japanese language mainly exposed by looking at the mora in literature point of view. The object that being used is a novel called “Narcissu” by the Japanese Author, Tomo Kataoka. The purpose of writing this article is to describe the disipation in Mora in Japanese language written in the form of literature. The research method used in this research is descriptive method. In analyzing the data, the author use the reference theory based on Morphology byIori Isao. The use of theories help the author to get to the conclusion that in Japan’s daily conversation, the use of proper full mora in term of verb seldom been mention. The result of this studies show that the reason of the Mora dissipation in conversation is because of the implicitory in term of talking. In other words, it can be seen that Japanese language speaker often not using the proper word on their conversation mainly because there’s a mutual understandment in term of implicitory word that keep them talk with less word.